PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGGELAPAN PAJAK - - Reskino; - Rini; Dinda Novitasari (Universitas Trunojoyo Madura, 2014)
This research aims to test university accounting students perception in tax evasion, which the respondents in this research were undergraduate and graduate accounting students in Jakarta. Total sample of this research was 121 respondents. The determination method sample that used is purposive sampling with judgement sampling, to test the hypothesis in this research.Researchers use different independent samplet-test. This research shows that there is no different perception between undergraduate and graduate accounting students in terms of tax evasion.